Impact of polymer aging on main‐chain poly(fullerene)s with halide chain‐ends for inverted perovskite solar cells - Paulin, João V. [UNESP]; Nogueira, Gabriel L. [UNESP]; Santos, Douglas H. N. [UNESP]; Gomes, Marco Antônio G. B.; Carvalho‐Jr, Valdemiro P. [UNESP]; Filho, Luiz C. Silva [UNESP]; Hiorns, Roger C.; Graeff, Carlos F. O. [UNESP] (Wiley, 2025)
Abstract As perovskite solar cells (PSCs) advance toward commercialization, the need for stable and easily processable materials becomes increasingly important. In this study, we examine how the aging of polymeric electron transport layers (ETLs) affects the performance of inverted PSCs. Two main‐chain poly(fullerene)s, PC 60 DB (IMP) and PC 60 DB (ATRAP) , which differ only in their terminal halogen groups, were stored under nitrogen, in the dark and at room temperature, for up to 11 months before device fabrication. Devices using aged PC 60 DB (IMP) showed significant drops in efficiency, while those based on PC 60 DB (ATRAP) maintained more stable performance and even exhibited reduced hysteresis over time. These contrasting results appear to stem from differences in halogen reactivity, with iodine likely triggering degradation pathways not seen in the bromine‐containing counterpart. Altogether, the findings highlight how thoughtful molecular design can improve the long‐term stability and practical use of ETL materials in scalable PSC technologies. © 2025 The Author(s). Polymer International published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.